The Relationship Between Transactional Leadership, Conflict in the Work Team, Personality and Job Stress - Ayuningrum, Adelia (2014)
The main objective of this study is to examine the influence of transactional leadership, conflict in the work team and personality on job stress. In order to measure that, transactional leadership, conflict in the work team and personality were used. Data were gathered through questionnaire survey of employee at PT Semen Baturaja head office (n=130). Correlation and regression result analysis were used to examine the relationship between independent variables which are transactional leadership, conflict in the work team and personality and dependent variable which is job stress. The result indicated that all the independent variables which are transactional leadership, conflict in the work team and personality were positively correlated to job stress. The regression result revealed that 43.6% of job stress has been significantly explained by transactional leadership, conflict in the work team and personality. Moreover, the result showed that the most influencing factor that causing job stress was conflict in the work team. The findings were discussed and recommendations for future research and practitioners were also addressed.